2021
DOI: 10.1038/s41386-021-01006-5
|View full text |Cite
|
Sign up to set email alerts
|

Incerto-thalamic modulation of fear via GABA and dopamine

Abstract: Fear generalization and deficits in extinction learning are debilitating dimensions of Post-Traumatic Stress Disorder (PTSD). Most understanding of the neurobiology underlying these dimensions comes from studies of cortical and limbic brain regions. While thalamic and subthalamic regions have been implicated in modulating fear, the potential for incerto-thalamic pathways to suppress fear generalization and rescue deficits in extinction recall remains unexplored. We first used patch-clamp electrophysiology to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 65 publications
1
22
0
Order By: Relevance
“…Wang et al reported that parvalbumin (PV)-positive neuronal projections from the ZI to the Po (ZI-Po) are critical for promoting nocifensive behaviors . We cannot rule out the possibility that ZI TH + neurons have local connections with GABA neurons that modulate freezing behavior through nocifensive adjustment (Chou et al, 2018;Venkataraman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported that parvalbumin (PV)-positive neuronal projections from the ZI to the Po (ZI-Po) are critical for promoting nocifensive behaviors . We cannot rule out the possibility that ZI TH + neurons have local connections with GABA neurons that modulate freezing behavior through nocifensive adjustment (Chou et al, 2018;Venkataraman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A13 neurons also project to the paraventricular nucleus of the thalamus (Li et al, 2014;Otake & Ruggiero, 1995), periaqueductal grey (Messanvi et al, 2013) and the mesencephalic locomotor region (Sharma et al, 2018). Although recent evidence has associated the A13 neurons with both conditioned fear through projections to thalamus (Brandao & Coimbra, 2019;Venkataraman et al, 2021) and nociception through projections to periaqueductal grey and central amygdala (Moriya & Kuwaki, 2021), there is a paucity of evidence elucidating the functional role of A13 dopaminergic neurons in SC.…”
Section: Mechanisms Of Reward-related Modulation Of Activity In the Superior Colliculusmentioning
confidence: 99%
“…It is tempting to speculate that input from A13 could represent the source of modulation to the bottom-up information streaming into the SC. Notably, this may involve not only dopaminergic mechanisms because, like midbrain dopamine neurons, A13 neurons have recently been shown to co-release GABA into target areas (Venkataraman et al, 2021). This modulation could act in series with the disinhibition from the caudate, where the visual response is first sensitized to reward prediction in the superficial layers, receiving further top-down modulation via the caudate and cerebral cortex when determining a motor response.…”
Section: Mechanisms Of Reward-related Modulation Of Activity In the Superior Colliculusmentioning
confidence: 99%
“…Activation of ZI or targeted stimulation of GABAergic cells in the ZI attenuates fear generalization and enhances extinction recall. Targeted activation of the dopaminergic ZI projection to thalamic reunions has no effect on fear generalization but enhances extinction recall in a dopamine receptor D1-dependent manner (Venkataraman et al, 2019(Venkataraman et al, , 2021. Silencing of ZI or specifically suppression of the ZI PV + neurons blocks fear conditioning memory acquisition and remote retrieval (Zhou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%